Immunoendocrinology scientific and clinical aspects - Eisenbarth, George S. (Contemporary endocrinology., 2009)
Immunoendocrinology is a rapidly developing field of research that seeks to understand the intersection of the immune and endocrine systems. Immunoendocrinology: Scientific and Clinical Aspects explores in detail the current knowledge of immunoendocrinology, namely endocrine disorders produced by disorders of immune function. Chapters cover both basic pathophysiology informed by studies of animal models as well as current understanding of multiple related clinical diseases?their pathophysiology, diagnosis, and therapy. Immunoendocrinology: Scientific and Clinical Aspects captures the central role of immunoendocrinologic processes in the pathogenesis of not only type 1 diabetes but in a range of other autoimmune and endocrine disorders.